PENGEMBANGAN MEDIA KOMIK BRILIAN BERBASIS PEMBELAJARAN MULTILITERASI - Rizkiyani, Nurafiah; Syachruroji, Ahmad; Setiawan, Sigit (Jurnal keilmuan dan Kependidikan dasar, 2022)
This study aims to develop a learning product in the form of Brilliant Comics based on Multiliteracy learning for Grade IV Elementary School. The place of this development research is at SD Negeri Kembangan Utara 09. The subjects of this research are fourth grade elementary school students. The research model used is the Research & Development model from Sugiyono (2015). While the data collection techniques through interviews, preliminary studies, questionnaire collection, and documentation. Brilliant Comic Media has passed the validation stage with an average percentage score of 90.75% from the media expert team in the "Very Eligible" category, the material expert team at 93% in the "Very Eligible" category, the linguist team at 90.85 % with the category "Very Eligible". In the limited trial for class IV D, the average percentage value of student responses was 96.7% in the "Very Good" category. Based on these scores, it shows that the development of Brilliant Comics media based on Multiliteration Learning is declared feasible to be developed and used in fourth grade elementary school students and can be scientifically justified.